Medical retina : update 2017 - Bandello, Francesco (ESASO course series / series editors F. Bandello, B. Corcóstegui, 2017)
In the 'ESASO Course Series' the essentials of the courses of the European School for Advanced Studies in Ophthalmology (ESASO) are made available to interested ophthalmologists, optometrists, technicians, and residents all over the world. In the seven years since the first edition of this book was published, major advances in diagnostics and management strategies of retinal diseases have evolved. This updated and revised edition takes this into account and focuses on the significant developments of preferred practice for diabetic retinopathy and dry and neovascular AMD. It further discusses pathology, imaging, and visualization of retinal diseases. In addition it considers biologic disease markers and new drugs being developed. Medical retina specialists who wish to stay abreast of the constantly changing world of medical retina will find this publication a must-read.